Association between dietary acid load and cancer risk and prognosis: An updated systematic review and meta-analysis of observational studies - Wang, Ran; Wen, Zhao-Yan; Liu, Fang-Hua; Wei, Yi-Fan; Xu, He-Li; Sun, Ming-Li; Zhao, Yu-Hong; Gong, Ting-Ting; Wang, Hui-Han; Wu, Qi-Jun (Frontiers in Nutrition, 2022)
Epidemiological studies have suggested dietary acid load (DAL) might be related to the risk and prognosis of cancer, whereas the evidence is contentious. Several high-quality observational studies have been published following a prior systematic review with only one study was included. Consequently, we conducted an updated systematic review and meta-analysis to comprehensively investigate the relationship between DAL and cancer risk and prognosis. A systematic literature search was conducted in PubMed, Embase, and Web of Science databases from inception to 26 October 2021. Summary relative risks (RRs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Publication bias, subgroup, meta-regression, and sensitivity analyses were also conducted. Ten observational studies (six cohorts and four case-control studies) with 227,253 participants were included in this systematic review and meta-analysis. The summary RRs revealed a statistically significant associations between DAL and cancer risk (RR = 1.58, 95% CI = 1.23-2.05, I2 = 71.9%, n = 7) and prognosis (RR = 1.53, 95% CI = 1.10-2.13, I2 = 77.1%, n = 3). No evidence of publication bias was observed in current analysis. Positive associations were observed in most subgroup analyses stratified by predefined factors, including region, study design, study quality, study population, participants' gender, age of participants, cancer type, DAL assessment indicator, and adjustment of potential confounding parameters. No evidence of heterogeneity between subgroups was indicated by meta-regression analyses. The high DAL might be associated with an increased risk of cancer as well as a poor prognosis of cancer. More high-quality prospective studies are warranted to further determine the associations between DAL and risk and prognosis for specific cancers.